Design of Patrol Unmanned Aerial Vehicle Based on MPU9250. Issue 1 (January 2021) - Tang, Yanfeng; Lin, Songbin
Abstract: To improve the attitude control accuracy of quadcopter UAVs, a patrol UAV with STM32 as the main controller and MPU9250 as the attitude detection module is designed in this paper. For attitude control part, a kind of attitude control algorithm which preprocesses by extended Kalman filter algorithm is designed and then a cascade PID control algorithm is adopted. The test flight results show that the UAV can achieve functions of lifting, rolling, pitching, yawing and hovering.